Peran Vitamin D dalam Retinopati Diabetik - Michelle Amelia Tanian; Felix Rowan; Santi Anugrahsari; Rendy Damar Nugraha (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2023)
Diabetic retinopathy (RD) is the most common microvascular complication and can cause visual impairment and even blindness. Various studies show a relationship between vitamin D deficiency and increased incidence of RD. The purpose of this scientific paper is to explore the role of vitamin D in relation to RD so as to open opportunities for further knowledge and research. Research Methods using Literature Review, by searching PubMed and Google Scholar, with keywords in English